2021
DOI: 10.20527/btjpm.v3i1.1803
|View full text |Cite
|
Sign up to set email alerts
|

Pelatihan Pengembangan Bahan Ajar Elektronik (E-Book) di SMKN 1 Banjarmasin

Abstract: Permasaalahan yang di hadapi oleh mitra/guru-guru SMKN 1 Banjarmasin adalah masih banyak guru yang belum memiliki pengetahuan mengenai cara mengembangkan bahan ajar, minimnya keterampilan guru dalam menulis bahan ajar, dan rendahnya motivasi guru untuk menulis bahan ajar. Oleh karena itu tim pengabdian masyarakat Program Studi Teknologi Pendidikan FKIP ULM membantu guru-guru SMKN 1 Banjarmasin dalam mengembangkan bahan ajar elektronik (digital), melalui kegiatan pelatihan. Tujuan pelatihan ini adalah meningkat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…to increase teacher creativity in making electronic book-based teaching materials and improve learning activities in the midst of the covid-19 pandemic (Ambarita, 2020). In order to increase the knowledge and skills of teachers in compiling and writing teaching materials both in physical and electronic form (e-books), training in community service activities was held at SMKN 1 Banjarmasin (Rafiudin et al, 2021). Based on the results of previous research, it can be seen the effectiveness of the training activities for the preparation of online and face-to-face teaching materials.…”
Section: Evaluation and Monitoringmentioning
confidence: 99%
“…to increase teacher creativity in making electronic book-based teaching materials and improve learning activities in the midst of the covid-19 pandemic (Ambarita, 2020). In order to increase the knowledge and skills of teachers in compiling and writing teaching materials both in physical and electronic form (e-books), training in community service activities was held at SMKN 1 Banjarmasin (Rafiudin et al, 2021). Based on the results of previous research, it can be seen the effectiveness of the training activities for the preparation of online and face-to-face teaching materials.…”
Section: Evaluation and Monitoringmentioning
confidence: 99%
“…And we need a detailed explanation of how to comprehend KI and KD, KD nature especially skills". if that explains not of the field of physical education, sport, and health (PJOK), but from other fields of study (Rafiudin et al, 2021).…”
Section: Figure 1 the Preparation Capabilities Teachers At Workhop Pr...mentioning
confidence: 99%
“…The skill of developing teaching materials, as mandated by the Minister of National Education, has been taught in courses at many Educational Personnel Education Institutions (Lembaga Pendidikan Tenaga Kependidikan / LPTK) as an effort to prepare pre-service teachers to become teachers who meet the required competencies. However, based on several studies related to writing skills of teaching materials that have been carried out, it showed that the ability of preservice teacher in compiling teaching materials was still lacking (Sukawati, Ismayani, & Permana, 2019), even many teachers still lack knowledge in writing teaching materials (Rafiudin, et al, 2021). Other researchers stated that low competence in writing teaching materials for teachers due to low theoretical knowledge of teaching materials and low interest in writing teaching materials (Asniati & Syamsuri, 2021) and the teaching materials made by the teacher were good, but there were several components that were not completely covered the scope of teaching materials based on state curriculum standards (Handayani, S., Halidjah, S., & Ghasya, 2021) and…”
Section: Introductionmentioning
confidence: 99%